E-CRM BASED ON INSTAGRAM SOCIAL MEDIA AS A MUSEUM PROMOTION FORUM - Amali, Muhammad Ikhlasul (PERSPEKTIF: Journal of Social and Library Science, 2024)
In practice, Customer Relationship Management can use various types of media, including digital media. Digital media is considered effective because society in this modern era cannot be separated from the influence of technology. The use of technology in Customer Relationship Management can be done in various ways, one of which is through social media networks. Social media itself is a network that connects accounts within it, these accounts can represent individuals or groups of individuals, gathered either in organizations or institutions. This research uses the SLR method and collects 10 journals from 1100 journals found in the publish n perish application. This research results that Instagram, CRM and promotions are closely related to attracting museum visitors to return to visit the museum.